Connective Class Politics and Climate Justice: Challenges of Contemporary Left Politics (PROKLA. Journal of Critical Social Science, 2022)
Intersectional, connective (working) class politics, climate justice and a new perspective of economic democracy need to be at the center of renewed left and socialist politics. This is not only a programmatic issue for the Left Party, but party politics itself need to be renewed to provide space for people with different class experiences to come together and to organize for self-representation. The crystallization point of connective class politics is a socio-ecological system change: How can production be changed from the chaotic nature of accumulation to a democratically decided level of satisfaction of needs. Among his other writings Alex Demirovic’s work on economic democracy, among other things, provides important impulses for this goal.
Keywords: Left Party; Intellectuals; Socio-ecological System Change; Economic Democracy; Socio-Ecological System Change